Статично визначені просторові системи приводів типу механізма гексапода - Струтинський, С. В.; Яхно, О. М.; Strutinsky, S.; Jahno, О. (КНТУ, 2014)
Розглянута характерна конструкція просторової системи приводів у вигляді механізма-гексапода, яка використовується для встановлення навісного обладнання трактора. Виконано аналіз можливих схемних рішень механізма, що відрізняються різною кількістю суміщених шарнірних опор. Сформульовані раціональні умови статичної рівноваги механізму у вигляді сум моментів сил відносно деяких вісей, які проходять через характерні точки механізму. Показано, що статично визначений механізм має раціональні умови рівноваги у вигляді трьох систем рівнянь із двома невідомими кожна. Запропонована спрощена розрахункова схема, яка дозволяє в загальному вигляді розв’язати задачу статики просторової системи приводів. Спрощена схема є приведенням просторового механізма до плоского. З використанням спрощеної схеми досліджена статика просторової системи приводів типу механізма-гексапода. Визначено зусилля в ланках механізму, які виникають під дією гравітаційних сил та силових факторів, які описують корисне навантаження на систему. The characteristic design of a spatial system drives as mechanism-gexapod used to establish tractor attachments. The analysis of possible circuit design mechanisms that differ different number of combined hinge supports. Formulated rational conditions of static equilibrium mechanism. It is shown that in general the problem of static spatial drive systems are statically indeterminate. Among the mechanisms that have six units of variable length has a group of statically-defined. They are the basis for a rational space of drives. A special static-equilibrium conditions defined system as the sum of the moments of forces with respect to some axis that runs through the feature points of the mechanism. It is shown that statically defined mechanism is rational equilibrium conditions in three systems of equations with two unknowns each. Rational equilibrium conditions greatly simplify the solution of problems of statics. This is especially true mechanisms to position close to singular. Static solution of the problem in general terms, is time consuming. Therefore, the proposed simplified calculation schemes that allow a general way to solve the problem of static spatial system drives. A simplified scheme is bringing spatial mechanism to flat. A simplified scheme is built for mechanisms to the plane of symmetry and load that acts in this plane. By the simplified scheme given approximately mechanisms arbitrary configuration. The analysis of the geometry and kinematics of the mechanism for its simplified scheme. Using the simplified scheme investigated static spatial system drive-type mechanism gexapod. Determined efforts to link mechanism arising under the influence of gravitational forces and security factors that determine the payload on the system. Useful load is presented in the form of power and steam action plane coincides with the plane of symmetry mechanism. For specific implementation mechanism set changes its geometric and force parameters that occur when you change the length of the drive. Determined how the position of individual components of the system and its center of mass. The effect of changing the length of each of the parts of the path of movement of the center of mass. This effect is nonlinear and depends on the initial configuration mechanism. The regularities of the so-called system of elementary movements, which are caused by changes in the length of each drive. Showing the effect of changing the sign payload efforts in some occasions. The conditions of linear dependence effort in the drive from the system parameters. Based on this set ranges rational moves some occasions.
Statically defined spatial system drives type mechanism hexapod
Keywords: просторові приводи; механізм-гексапод; схема; рівновага; рівняння; спрощена схема; кінематика; статика; spatial actuators; mechanism-gexapod scheme; balance the equation; simplified; kinematics; statics